Advocacy for Increased International Efforts for Antimicrobial Stewardship Actions in Low-and Middle-Income Countries on Behalf of Alliance for the Prudent Use of Antimicrobials (APUA), Under the Auspices of the International Society of Antimicrobial Chemotherapy (ISAC) - Tattevin, Pierre; Levy Hara, Gabriel; Toumi, Adnene; Enani, Mushira; Coombs, Geoffrey; Voss, Andreas; Wertheim, Heiman; Poda, Armel; Daoud, Ziad; Laxminarayan, Ramanan; Nathwani, Dilip; Gould, Ian (Frontiers in Medicine, 2020)
Antimicrobial stewardship (AMS) is a set of coordinated strategies to improve the use of antimicrobials, to enhance patient outcomes, reduce antimicrobial resistance, and decrease unnecessary costs. The pioneer years of AMS were restricted to high-income countries (HIC), where overconsumption of antibiotics was associated with emergence of multidrug-resistant (MDR) bacteria. AMS in low- and middle-income countries (LMIC) is also necessary. However, programs effective in HIC may not perform as well in LMIC, because (i) While decreased consumption of antibiotics may be an appropriate target in overconsuming HIC, this may be dangerous in LMIC, where many patients die from the lack of access to antibiotics; (ii) although AMS programs in HIC can be designed and monitored through laboratory surveillance of resistance, surveillance programs are not available in many LMIC; (iii) the heterogeneity of health care systems implies that AMS programs must be carefully contextualized. Despite the need to individually tailor AMS programs in LMIC, international collaborations remain highly valuable, through the dissemination of high-quality documents and educational material, that may be shared, adapted where needed, and adopted worldwide. This process, facilitated by modern communication tools, combines many benefits, including: (i) saving time, a precious dimension for health care workers, by avoiding the duplication of similar works in different settings; (ii) taking advantage of colleagues skills, and initiatives, through open access to the work performed in other parts of the world; (iii) sharing experiences, so that we all learn from each others' successes and failures.